Influence of excited molecules N₂(A³Σu⁺), N₂(B³Πg), O₂(¹Δg) and O₂(b¹Σg⁺) on ozone and hydroxyls (H₂O₂, OH, HO₂) kinetics in the plasma of barrier discharge in air at atmospheric pressure - Kalyuzhnaya, A.G.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
The kinetics of the N₂(A³Σu⁺), N₂(B³Πg), O₂(¹Δg) and O₂(b¹Σg⁺) excited states in the barrier-discharge plasma in atmospheric air is calculated and their effect on the concentrations of derivative products – ozone and hydroxyls OH, НO₂ and H₂O₂ is analyzed. It is shown that the largest deviations in the concentrations obtained with and without taking into account the excited states are observed for H₂O₂ (≈60%) and О₃ (≈ 40%) at a relative humidity of 20%. The variation of the air humidity from 20…80% does not result in qualitative changes in the behavior of the ozone and hydroxyl concentrations in the barrier discharge.